USING TALKING CHIPS STRATEGY TO IMPROVE STUDENTS’ SPEAKING ABILITY AT ELEVENTH GRADE STUDENTS OF SMK SENTOSA BHAKTI BATURAJA - Santi Puryani; Novarita Novarita; Yunda Lestari (Journal of Language Education (JoLE), 2021)
This study is aimed at improving XI students’ speaking abilit y of SMK Sentosa Bhakti Baturaja through the use of Talking Chips. The use of Talking Chips is expected to improve students’ speaking ability. This study was categorized as an experimental research. Pre-experimental design was used in this study. There was one class for Tryout and one class as a treatment class. The population of this study was 315 and the sample was 34 students in TKJ2 class. They have been selected by using cluster random sampling. The students’ taught by using Talking Chips strategy. The data were presented in the form of transcripts. The data collected by oral test. To check whether the application of instruction run well, it was designed the students were evaluated by using paired sample t-test. The result of paired sample t-test showed that there is a significant difference between students’ score in pre-test and post-test. The result of the study shows that Talking Chips improved the teaching of speaking and the students’ speaking ability. The mean scores of pretest was 59.76 while the mean scores of post-test was 69,59. It indicates that there was a statistical difference between the mean scores of the pre-test and the post-test. This implies that there was significant improvement of students’ speaking abilit y by using talking chips strategy to the Eleventh Grade Students of SMK Sentosa Bhakti Baturaja.